2016
DOI: 10.17533/udea.rccp.v29n4a06
|View full text |Cite
|
Sign up to set email alerts
|

Growth and pre-weaning mortality of Katahdin lamb crosses

Abstract: SummaryBackground: Katahdin breed sheep is highly disseminated in Mexico. This breed and its crosses have recently gained attention among sheep producers. However, research with crosses between Katahdin and other meat breeds is limited. Objective: to evaluate the genetic and non-genetic factors affecting growth and mortality rate of crossbred lambs from Katahdin ewes fecundated with breeds specialized for meat production. Methods: crossbred lambs (n = 152) from Katahdin ewes sired with Hampshire (KH; n = 43), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
2
11
2
2
Order By: Relevance
“…These results agree with Abdullah & Tabbaa (2011), who found that weaning weight for F 1 Chios-Awassi lambs did not differ from purebred Awassi lambs. However, Mellado et al (2016) reported that crossbred Dorper-Turcana lambs were heavier at weaning than the purebred Turcana lambs. Birth weight is related directly to the genetics and nutrition of the pregnant ewe.…”
Section: Resultsmentioning
confidence: 97%
“…These results agree with Abdullah & Tabbaa (2011), who found that weaning weight for F 1 Chios-Awassi lambs did not differ from purebred Awassi lambs. However, Mellado et al (2016) reported that crossbred Dorper-Turcana lambs were heavier at weaning than the purebred Turcana lambs. Birth weight is related directly to the genetics and nutrition of the pregnant ewe.…”
Section: Resultsmentioning
confidence: 97%
“…Lambs were raised and observed in 100 flocks across the United States with different management systems that may have introduced greater weight variations than the present forage-based system. Several other studies varying in breed and environment confirm this general trend in body weight in young animals, but vary in magnitude ( Carrillo and Segura, 1993 ; Akpa et al, 2006 ; Stafford et al, 2007 ; Mellado, 2016 ). Some studies propose that birth type primarily influences birth weight and becomes less important as animals age ( Jucá et al, 2016; Pesántez-Pacheco et al, 2019 ).…”
Section: Resultsmentioning
confidence: 68%
“…Al respecto, Bores-Quintero et al (2002) observaron que durante la etapa postdestete la GDP de los machos superó (P<0.05) en 27 % a la GDP de hembras, mientras que De Vargas Junior et al (2014), Schanbacher et al (1980 y Ghafouri-Kesbi y Notter (2016) concluyen que las diferencias en el peso y desarrollo entre los corderos y corderas reflejan la diferencia en el entorno endocrino y requerimientos de nutrientes entre los sexos. Las crías nacidos en parto simple presentaron una mayor tasa de crecimiento pre-destete con respecto a aquellos de parto múltiple, lo cual coincide con lo reportado previamente por Garduño et al (2002), Mellado, et al (2016) y Simeonov et al, (2014. Sin embargo, los corderos de parto múltiple compensaron el menor crecimiento previo al destete y obtuvieron una mayor GDP post-destete para terminar con un peso ajustado a 145 d similar al de los corderos nacidos en parto sencillo.…”
Section: Discussionunclassified